Cochlear resident macrophage mediates development of ribbon synapses via CX3CR1/CX3CL1 axis - Song, Xinyu; Li, Yang; Guo, Rui; Yu, Qianru; Liu, Shan; Teng, Qi; Chen, Zhong-Rui; Xie, Jing; Gong, Shusheng; Liu, Ke (Frontiers in Molecular Neuroscience, 2022)
Abstract In order for cochlear ribbon synapses formed between spiral ganglion neurons (SGN) and inner hair cells (IHC) to reach auditory maturation in postnatal mice, they must undergo significant morphological and functional development.However, the mechanisms underlying this cochlear ribbon synapse remodeling process remain unclear. Here, we report that cochlear resident macrophage via CX3CR1/CX3CL1 axis is essential for cochlear ribbon synapses in mice to develop and mature. In this study, significantly high levels of CX3CR1 expression (a macrophage surface-specific receptor) as well as significantly high levels of macrophage numbers were found in the cochlea from postnatal day 7, followed by a decrease from day 14 to day 28. On day 7, treatment of mice with CX3CR1 inhibitors for 7 days and artificial upregulation of CX3CL1 levels in the inner ear environment using the semicircular canal injection technique, respectively, resulted in a significant increase in hearing threshold on day 28. In addition, abnormalities in the morphology and number of cochlear ribbon synapses were detected from day P14, which may be associated with hearing impairment. Thus, our study suggests that macrophage regulation of cochlear ribbon synapse remodeling via CX3CR1/CX3CL1 axis is required during hearing development and offers a fresh viewpoint on immune-related hearing loss throughout auditory development. A new treatment target for sensorineural hearing loss is also provided by us.